The influence of commitment, entrenchment and support of transfer on the impact of training at work - Balsan, Laércio André Gassen; Costa, Vânia Medianeira Flores; Bastos, Antonio Virgílio Bittencourt; Lopes, Luis Felipe Dias; Lima, Mauren Pimentel; Santos, Andressa Schaurich dos (Revista de Administração da UFSM, 2018)
This article aims to identify the influence of organizational commitment and entrenchment, as well as support for the transfer of training on the impact of on-the-job training. For this, a sample of 392 servers from a public institution of higher education who responded to a questionnaire prepared from previously validated self-assessment models was used. After quantitatively analyzing the data, the results showed positive correlations between affective commitment, the impact of training and support to transfer at work; and negative correlations between the training impact at work and the dimensions of entrenchment (limitations of alternatives and bureaucratic arrangements). It was concluded, therefore, that the nature of the individual’s link with the organization differently affects the transfer of the learning obtained in the trainings, which can subsidize strategies for the strengthening of the training impact at work. This article aims to identify the influence of organizational commitment and entrenchment, as well as support for the transfer of training on the impact of on-the-job training. For this, a sample of 392 servers from a public institution of higher education who responded to a questionnaire prepared from previously validated self-assessment models was used. After quantitatively analyzing the data, the results showed positive correlations between affective commitment, the impact of training and support to transfer at work; and negative correlations between the training impact at work and the dimensions of entrenchment (limitations of alternatives and bureaucratic arrangements). It was concluded, therefore, that the nature of the individual’s link with the organization differently affects the transfer of the learning obtained in the trainings, which can subsidize strategies for the strengthening of the training impact at work.